If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+4(3-k)=2(-2k+9)
We simplify the equation to the form, which is simple to understand
6+4(3-k)=2(-2k+9)
Reorder the terms in parentheses
6+(+12-4k)=2*(-2k+9)
Remove unnecessary parentheses
+6+12-4k=+2+*(-2k+9+)
Reorder the terms in parentheses
6+12-4k=+(-4k+18)
Remove unnecessary parentheses
+6+12-4k=-4k+18
We move all terms containing k to the left and all other terms to the right.
-4k+4k=+18-6-12
We simplify left and right side of the equation.
k=0
0=0
This equation is an identity, so all real numbers are solutions.
| 12=3v-15 | | 8p-8=10-3p | | 5-2y=y | | 4x^2-9x+11=2x+5 | | 8x^3+24x-24x^2-8=0 | | 4x^2+24x+8=0 | | 2x^3+3x^2-12x-10=0 | | x^2+10x+39=-5x-5 | | 6k-5k+10-18= | | h^2+10h=21 | | 7t+3t=30 | | 7t+3t=11 | | 5x+39=28 | | 7.32=.05x-.18 | | 8x-1=4x+23 | | 20x+41=-199 | | 9x+40=-14 | | 13.8=x-2.4 | | y=x^2-10x-21 | | 14x+3=-25 | | 7y+4(3-y)=18 | | x^3+18*x+6=0 | | -4x-12=-36 | | (-3x-6)(7x+3)= | | 1A+2B+3C=30 | | 2(x+7)-7=9 | | 5-x=3(x-1) | | -2(x+3)=20 | | 24-10x=9 | | 5x-4y=17 | | n^4-n^3-n+1=0 | | -2x+3y=52 |